Pengembangan Lembar Kerja Peserta Didik (LKPD) PJOK Senam Lantai Meroda Berbasis Penguatan Pendidikan Karakter Untuk Peserta Didik Kelas VII SMP Negeri 18 Kota Bengkulu - Muhammad Nuryogatama; Tono Sugihartono; Ari Sutisyana (SPORT GYMNASTICS : Jurnal Ilmiah Pendidikan Jasmani, 2020)
Lembar Kerja Peserta Didik (LKPD), is research and development that is commonly called (R&D). The subjects of this study were Students of grade VII of SMP Negeri 18 Bengkulu City with 27 students and 2 teachers. Data analysis techniques using quantitative descriptive analysis as outlined in the form of percentages. Data collection instruments and techniques with a questionnaire. The results of the study stated that the products developed were feasible with expert validation scores, , in expert I, Content eligibility aspects "very good" 100%, aspects of conformity with character education "very good" 97%, didactic aspects "very good" 93%, construction aspects "very good" 100% and technical aspects "very good" 93%. whereas the final result of the assessment was conducted by expert II, the aspect of Feasibility of "very good" content was 100%, the suitability aspect of Character Education was "very good" 97%, the Didactic aspect was "very good" 100%, the construction aspect was "very good" 100% and the technical aspect was "very good” 96%. While overall the quality of LKPD percentage of students' responses to LKPD based on Character Education is "very good" with a percentage of 86% and the results of teacher responses are "very good" with a percentage of 93%.